Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Ocular Pharmacokinetic Study Using T1 Mapping and Gd-Chelate- Labeled Polymers - Xianfeng Shi; Xin Liu; Xueming Wu; Zheng-Rong Lu; S. Kevin Li; Eun-Kee Jeong (Pharmaceutical Research, 2011)

LysGH15B, the SH3b Domain of Staphylococcal Phage Endolysin LysGH15, Retains High Affinity to Staphylococci - Jingmin Gu; Rong Lu; Xiaohe Liu; Wenyu Han; Liancheng Lei; Yu Gao; Honglei Zhao; Yue Li; Yuwen Diao (Current Microbiology, 2011)

Increased production of succinic acid in Escherichia coli by overexpression of malate dehydrogenase - Li-ya Liang; Rong-ming Liu; Jiang-feng Ma; Ke-quan Chen; Min Jiang; Ping Wei (Biotechnology Letters, 2011)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Usefulness of Enhanced Power Doppler Imaging in Monitoring Acral Microcirculation in Type 2 Diabetes Mellitus and its Complications - Fang Ma; Baozhen Zhao; Huiping Zhang; Wei-Ping Li; Yuan-Yuan Liu; Yuan-Yuan Dang; Rong Wu; Le Hang Guo; Chen Lu (Cell Biochemistry and Biophysics, 2011)

Interleukin-6, but Not Soluble Adhesion Molecules, Predicts a Subsequent Mortality from Cardiovascular Disease in Patients with Acute ST-Segment Elevation Myocardial Infarction - Zhen-Xing Fan; Qi Hua; Yin-Ping Li; Rong-Kun Liu; Zheng Yang (Cell Biochemistry and Biophysics, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

cDNA cloning and characterization of 5′ upstream promoter region of porcine mef2c gene - Min Liu; De Quan Xu; Jian Peng; Rong Zheng; Fenge Li; Si Wen Jiang (Molecular Biology Reports, 2011)

Analysis of variable sites between two complete South China tiger (Panthera tigris amoyensis) mitochondrial genomes - Wenping Zhang; Bisong Yue; Xiaofang Wang; Xiuyue Zhang; Zhong Xie; Nonglin Liu; Wenyuan Fu; Yaohua Yuan; Daqing Chen; Danghua Fu; Bo Zhao; Yuzhong Yin; et al. (Molecular Biology Reports, 2011)

Halomonas qijiaojingensis sp. nov. and Halomonas flava sp. nov., two moderately halophilic bacteria isolated from a salt lake - Chao Chen; Rong Shi; Bing-Bing Liu; Yun-Jiao Zhang; Hong-Zhuan Sun; Chang-Tian Li; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Molecular characterization of a wheat -Thinopyrum ponticum partial amphiploid and its derived substitution line for resistance to stripe rust - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Zu-Jun Yang (Journal of Applied Genetics, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Spectroscopic and Microscopic Studies on the Mechanisms of Mitochondrial Toxicity Induced by Different Concentrations of Cadmium - Yue Zhang; Jia-Han Li; Xiao-Rong Liu; Feng-Lei Jiang; Fang-Fang Tian; Yi Liu (The Journal of Membrane Biology, 2011)

Synthesis, Characterization, DNA Binding Properties and Antioxidant Activity of Ln(III) Complexes with Schiff Base Ligand Derived from 3-Carbaldehyde Chromone and Aminophenazone - Yong Li; Zheng-yin Yang; Tian-rong Li; Zeng-chen Liu; Bao-dui Wang (Journal of Fluorescence, 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

Biophysical Studies on the Interactions of a Classic Mitochondrial Uncoupler with Bovine Serum Albumin by Spectroscopic, Isothermal Titration Calorimetric and Molecular Modeling Methods - Yue Zhang; Jia-Han Li; Yu-Shu Ge; Xiao-Rong Liu; Feng-Lei Jiang; Yi Liu (Journal of Fluorescence, 2011)

Mineral status and mechanical properties of cancellous bone exposed to hydrogen peroxide for various time periods - Dan Li; Long Bi; Guolin Meng; Jun Wang; Rong Lv; Min Liu; Jian Liu; Yunyu Hu (Cell and Tissue Banking, 2011)

Antigenically dominant proteins within the human liver mitochondrial proteome identified by monoclonal antibodies - YanFang Ju; JinJu Yang; Rong Liu; XiaoLan Liu; XueMei Du; Li Liu; ZhiCheng Chen; Jun Chi; ShuEr Liu; Yuan Gao; JianEn Gao; ShunChang Jiao; et al. (Science China Life Sciences, 2011)

Immunomodulative effects of mesenchymal stem cells derived from human embryonic stem cells in vivo and in vitro - Zhou Tan; Zhong-yuan Su; Rong-rong Wu; Bin Gu; Yu-kan Liu; Xiao-li Zhao; Ming Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.